The Model of Slovak Railway Strategy - Hittmar, Stefan (Communications - Scientific letters of the University of Zilina, 2008)
Rail transport plays akey role in transport services within adomestic and international scope. In the scope of social and economic changes and the dynamically developing transport sector, it is the task of railways to analyse and programmatically prepare its management. In the context of European and national traffic policy the strategy of Railways of the Slovak Republic (ZSR – Zeleznice Slovenskej republiky) identifies the need for successful technological and company development in the coming decades. This short paper of ZSR strategy contributes to better knowledge and apositive presentation of the direction of ZSR towards bodies of state administration and partner organizations within adomestic and international scope.